The Performance Improvement for Plenum Inside Intake Manifold in Automotive Vehicles Engine - Mat, Shafizal; Salim, Mohd Azli (2011)
Engine is the important parts in automotive vehicles. There are many types of engine that are available and used in vehicles in the market. Performance of engine is depending on the technology applied and it design concept. One of the components can effected the performance of the engine is intake manifold. In this research, it was studied the designation of intake manifold for existing design and it was proposed the new design which is the performance is better than the conventional. Computational Fluid Dynamics (CFD) software is used to analyze the air flow and pressure air inside the intake manifold especially for the plenum. According to this analysis, the proposed design was agreed to give more performance to the engine according to the high air flow and low pressure air, respectively. Due to these two parameters and open literature, there can give more performance to the engine during the operation.